Infectious Disease Consultation Is Associated with Decreased Mortality with Enterococcal Bloodstream Infections. (4th October 2017) - Lee, Rachael A; Vo, Daniel; Zurko, Joanna; Griffin, Russell; Rodriguez, J Martin; Camins, Bernard
Abstract: Background: Enterococcal bloodstream infections (EBSI) have been attributed with significant morbidity and mortality. The objective of this study was to determine whether IDC is associated with improved mortality in patients hospitalized with EBSI. Methods: This is a cross-sectional study of patients admitted to the University of Alabama Health System between January 1, 2015 and June 30, 2016 who had EBSI. Patients who died within 2 days of hospitalization were excluded. Categorical variables were analyzed with chi-square or Fisher's exact test and continuous variables were analyzed with a t -test or Wilcoxon rank-sums test when appropriate. A  P -value < 0.05 was considered significant. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CI) for factors associated with 30-day in-hospital mortality. Results: A total of 213 patients met the case definition. One hundred and thirty-four (63%) received IDC. Baseline patient demographics and comorbidities were similar in both groups. Patients with IDC were more likely to have repeated blood cultures (99% vs. 72%, P  < 0.001), echocardiogram performed (77% vs. 46%, P  < 0.001), and interventions for source control (19% vs 6%, P  = 0.01). Patients without IDC were more likely to have inappropriate antibiotic treatment or no antibiotics (20% vs. 0%, P  < 0.001) as well as inappropriate duration of therapy (54% vs. 10%, P  < 0.001). There were no differences in the rates of recurrent bacteremia or readmission within 60 days. Patients who did not receive IDC had higher 30-day in-hospital mortality (27% vs. 13%, P  = 0.02). Having an echocardiogram (OR 2.75, 95% CI 1.36–5.55), surgical intervention (OR 3.11, 95% CI 1.07–9.05) and an IV catheter (OR 3.90, 95% CI 1.39–10.88) were associated with increased likelihood of IDC while inappropriate duration of antibiotics was associated with an 87% decreased likelihood of IDC (OR 0.13, 95% CI 0.06–0.29). The strongest association observed with 30-day mortality was inappropriate duration of antibiotics (OR 4.93, 95% CI 1.93–12.61). Conclusion: IDC was associated with reduced 30-day in-hospital mortality in patients with EBSI. Although further investigation is warranted, the results of this study suggest that early involvement of ID specialists in EBSI may lead to better outcomes. Disclosures: All authors: No reported disclosures.